Factors related to scientific production in university teachers - Díaz Lazo, Aníbal Valentín (2019)
The generation of scientific production (SP) requires a personal and institutional motivational culture. Objective. To determine the factors related to SP made by teachers of a School of Medicine. Methods. The design was descriptive, prospective and transversal. The sample consisted of 65 teachers and it was collected in November 2014. They were surveyed with informed consent. The data was collected in a questionnaire. Results. 65 (100 %) teachers were included, average age 47 + - 8 years (range: 33-62). There were 60 (92.3 %) males. 98.5 %(64) consider that communication of research results is important, and 6.1 % publish in indexed journals. Teachers aged 30-49 years (80 %) performed the highest number of publications compared to those who were 50 years of ageor older (20 %) (OR = 5.0, 95 % CI: 1.4-17.3; p < 0.011). The main motivational factors with SP were: the increase in professional academic quality [44.6 % (29)], the generation of new knowledge [43.1 % (28)] and the achievement of personal satisfaction [7.7 % (5)]. The demotivational factors were: lack of time available [49.2 % (32)], ignorance of the scientific research methodology [13.6 % (9)] and lack of economic support [12.3 % (8)]. Conclusions. The main factor related to SP was having an age under 50, and the most frequent were motivational factors were to generate new knowledge and increase the professional academic quality.